Examining Indonesia's Nickel Downstream Policy Through Securitisation Theory - Nugraha, Aryanta; Madu, Ludiro; Mulyanto, Indro Herry (Jurnal Paradigma, 2025)
Indonesia's nickel downstream policy represents a strategic shift in its natural resource governance, characterized by its focus on adding value to raw nickel through domestic processing. We propose a securitisation/resource security framework to perspective to understand Indonesia's nickel downstream policy. Securitisation of natural resource is a process in which the government frames natural resources as an existential threat to state interests, which varies in nature and is highly dependent on certain conditions. This policy arises when natural resource problems can have an impact on economic security, regime security and/or geopolitical problems in a country. From the perspective of securitisation, the nickel downstream policy is one of the Indonesian government's responses to the perception of threats to economic security, regime/government security and security from geopolitical threats that arise both from the domestic and international levels. The research reveals that the Indonesian government has strategically employed securitization narratives to justify the measures, such as the export ban on raw nickel. These narratives highlight the critical role of nickel in driving economic growth, securing regime legitimacy, and navigating geopolitical competition in the context of the global clean energy transition. By integrating insights from securitisation theory, this study contributes to a deeper understanding of how natural resources are constructed as security issues in developing economies. It underscores the need for balancing economic and geopolitical ambitions with environmental and social considerations, offering a framework for analysing resource policies amid global energy transitions and shifting geopolitical dynamics.